Tumor-Szintigraphie mit 123J-markiertem Östradiol beim Mammakarzinom - Rezeptorszintigraphie - Scheidhauer, K.; Müller, S.; Smolarz, Kamilla; Bräutigam, P.; Briele, B. (Nuklearmedizin - NuclearMedicine, 1991)
The estrogen receptor (ER) status is an important factor for prognosis and endocrine therapy of breast cancer. Therefore 16-α-123l-lodestradiol-17-ß (123I-E2) as a receptor-specific radiopharmacon was used for scintigraphic tumor detection in 62 patients suspected of breast cancer. The studies were performed as a multicenter trial (5 university hospitals) to validate the method and to overcome methodical problems. A fast tracer elimination from the blood pool into the liver was seen, followed by biliary excretion allowing early imaging of the thorax due to low background activity but resulting in difficult imaging conditions of the abdomen. In 42 patients (30 carcinomas, 12 benign lesions) the overall sensitivity was 66% (ER status cut-off: 10 fmol/mg). Some patients with breast cancer showed focal or diffuse uptake in the area of primary lymph drainage (parasternal, axillary) without any clinical correlation, demanding follow-up investigations. There was only one false-positive result in a receptor-negative primary carcinoma; thus, the non-invasive determination of the ER status seems to be feasible. The sensitivity of 123I-E2 in the detection of primary breast cancer or metastases and recurrences is low compared to mammography and other methods; therefore, 123I-E2 scintigraphy cannot be used as a screening method. Differentiation of malignant and benign tissue is even more difficult as both may have a positive ER status, for example in mastopathia. Nevertheless, 123I-E2 scintigraphy is an in vivo imaging technique for the detection of breast cancer depending on the ER status and provides information about tumor localisation. It may become a specific method for the non-invasive diagnosis of the ER status and may be helpful in follow-up studies. As a receptor-specific agent 123I-E2 may give answers to questions of tumor heterogeneity and changes of the ER status during therapy.